Enfrentando o trauma em Maus, Black Dog e Chleb Wolnościowy - Kurtz, Karina Moraes (2024)
The corpus of this doctoral research is three comic books: Maus (1986), by Art Spiegelman; Black Dog: The Dreams of Paul Nash (2016), by Dave McKean; and Chleb Wolnościowy (2019), by Paweł Piechnik. All three works are graphic novels with trauma as their main theme, while Maus also evokes the theme of post-memory. Vladek (Maus) has his story of survival portrayed through the features and words of his son, Art (1986). Paul Nash, a British artist sent to the battlefield in the First World War, is portrayed from McKean's point of view (2016). The accounts of 11 survivors of the Majdanek concentration camp form the basis of the graphic novel by Pawel Piechnik (2019). The main objective of this thesis is to observe how trauma presents itself and can have repercussions in various areas of the lives of the protagonists of the comics analyzed. The secondary objective is to promote academic recognition of Black Dog and Chleb. Although Maus is widely known and researched, there is still no discussion in Brazil about the other two works. As a justification for these choices, we argue that this is a necessary analysis of the representation and artistic elaboration of trauma and its consequences on the subject, as well as traumas concerning people linked to someone who has experienced the traumatic event, as occurs in Maus. While Black Dog explores the effect of trauma on the protagonist's dreams, Chleb covers a different subject, showing the horror through the accounts of survivors. The trauma causes a rupture, interrupting the senses and meanings of the subject's personal narrative. After the period of shock, the characters find ways of dealing with the trauma so that they can survive the rupture inflicted on their identity. In the cases under analysis, art acted as a way of preserving the survivors' memories, being told and shown, with emphasis on moments when words were lacking to narrate the horror, so the lines, colors and shapes offer another way of telling a story. The methodology used is exploratory. It is a qualitative study of visual and narrative analysis and interpretation that used as its corpus three physical works that have already been published, but which have not yet been widely disseminated in Brazil, let alone in the academic world. The works are presented alongside a brief review of comics and the two world wars, as well as the Shoah. The works are analyzed in the light of the concepts of trauma, memory and post-memory and a brief discussion about the production of meaning in the area of Comparative Literature, based on the theoretical authors Paulo Ramos, Aleida Assmann, Marianne Hirsch, Jeanne-Marie Gagnebin, Márcio Seligmann-Silva, Tânia Franco Carvalhal, Antonio Candido, among others. Graphic novels create a literary genre that allows for new possibilities in relation to stories of survival, which can be seen in the works analyzed, which show how trauma is configured and how it crosses and damages several generations.